Nitrogen Use Efficiency of Rice Crop as Influenced by Planting Methods Under Glasshouse Condition - Harun, Muhamad (1985)
There response of nitrogen from the direct seeded rice in terms of yield increase and fertilizer use efficiency were studied under controlled glass house experiment. This was done to determine the effect of direct seeding technique on nitrogen fertilizer use efficiency as compared to the traditional transplanting method.